2022
DOI: 10.1021/acs.nanolett.2c02244
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembled Nanodot Actuator with Changeable Fluorescence by π–π Stacking Force Based on a Four-Armed Foldable Phthalocyanine Molecule and Its Supersensitive Molecular Recognition

Abstract: Designing intelligent molecules and smart nanomaterials as molecular machines is becoming increasingly important in the nanoscience fields. Herein, we report a nanodot actuator with changeable fluorescence by π–π stacking force based on a four-armed foldable phthalocyanine molecule. The assembled nanodot possessed a three-dimensional molecular space structure and multiple supramolecular interactions. The arms of the nanodot could fold and open intelligently in response to environmental molecular stimuli such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Configuration conversion‐induced ultra‐sensitive detection is currently a popular design method [24] . In 2022, Hu et al.…”
Section: Fluorescence Sensors For Metal Ionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Configuration conversion‐induced ultra‐sensitive detection is currently a popular design method [24] . In 2022, Hu et al.…”
Section: Fluorescence Sensors For Metal Ionsmentioning
confidence: 99%
“…Configuration conversion-induced ultra-sensitive detection is currently a popular design method. [24] In 2022, Hu et al reported a novel triazine-quinoline-appended 1,8-naphthalimide fluorescence sensor (5) that had a fluorescence quenching effect on Hg 2 + within 2 min in phosphate buffer/EtOH (v/v = 3/ 2) (Figure 3b). [25] Once the receptor at the C-4 position coordinated with Hg 2 + in 1 : 1, fluorescence emission intensity at 536 nm had a 14-fold decrease.…”
Section: Fluorescence Sensors For Metal Ionsmentioning
confidence: 99%
“…Yield: 91.85%; mp: 238-240 °C; FT-IR ν (cm −1 ): 3354, 3157, 3089, 2938, 2846, 1682, 1557, 1432, 1374, 1260, 1171, 966, 841, 769; 1 H NMR (600 MHz, DMSO-d 6 , δ ppm): 9.36 (s, 1H, -N + vCH-N-), 7.86 (s, 1H, -N-CHvCH-), 7.76 (s, 1H, -CHvCH-N + -), 7.44-7.56 (q, 4H, Ar-H), 5.51 (s, 2H, -CH 2 -), 3.93 (s, 2H, -CH 2 -), 3.88 (s, 3H, -CH 3 ), 2.68 (s, 2H, -CH 2 -), 1.75 (s, 6H, -CH 2 -). 13 13…”
Section: Synthesis Of the Ionic Liquid Molecules Containing An Extend...mentioning
confidence: 99%
“…They can be utilized in green reactions and processes, disease treatment, and novel material design. [11][12][13] Hydrogen peroxide (H 2 O 2 ) as an oxidative agent can produce free radicals and is widely used in the process of environmental disinfection, biomass bleaching and organic pollution treatment. Although the hydrogen peroxide molecule plays an important role in many green chemical reactions, its high activation energy and ineffective decomposition limit its efficiency in applications.…”
Section: Introductionmentioning
confidence: 99%
“…Advanced intelligent bionic interfaces assembled by nanoparticles with smart color changes by environmental stimuli have attracted much attention, which include photonic crystals with structural colors, photochromic materials, and force-chromic materials. Inspired by natural biological skin with intelligent color changes, wearable materials, artificial skin, and intelligent interior decoration with autocontrol of brightness and color transformation, including controllable moisture permeability and heat transfer, have important applications. Skin color changes and energy transfer in some animals, such as chameleons and octopuses, have inspired researchers to develop smart color-changing materials. …”
Section: Introductionmentioning
confidence: 99%